Introductory plant biology - Stern, Kingsley R. (McGraw - Hill, 2000)
This text offers students a solid introduction to the plant sciences. At an undergraduate level, the text material is well complimented by diagrams, photos, and drawings. Each chapter begins with a chapter outline and ends with review questions, discussion questions, chapter summaries, and additional readings.